Löse die folgenden biquadratischen Gleichungen ax4 + bx2 + c = 0

-9.5x4 + 161.5x2 - 684 = 0
 x1 = 2.83  x2 = -2.83
x3 = 3  x4 = -3
9.5x4 - 133x2 + 427.5 = 0
 x1 = 3  x2 = -3
x3 = 2.24  x4 = -2.24
-9.5x4 + 104.5x2 - 285 = 0
 x1 = 2.45  x2 = -2.45
x3 = 2.24  x4 = -2.24
2.5x4 + 25x2 + 62.5 = 0
 x1 = ◊  x2 = ◊
x3 = ◊  x4 = ◊
2x4 + 20x2 + 18 = 0
 x1 = ◊  x2 = ◊
x3 = ◊  x4 = ◊
-7x4 + 21x2 + 70 = 0
 x1 = 2.24  x2 = -2.24
x3 = ◊  x4 = ◊
4x4 + 16x2 - 240 = 0
 x1 = 2.45  x2 = -2.45
x3 = ◊  x4 = ◊
-9x4 + 45x2 = 0
 x1 = 0  x2 = 0
x3 = 2.24  x4 = -2.24
-9x4 - 153x2 - 648 = 0
 x1 = ◊  x2 = ◊
x3 = ◊  x4 = ◊
-x4 = 0
 x1 = 0  x2 = 0
x3 = 0  x4 = 0
9x4 - 81x2 + 72 = 0
 x1 = 2.83  x2 = -2.83
x3 = 1  x4 = -1
5.5x4 + 16.5x2 = 0
 x1 = 0  x2 = 0
x3 = ◊  x4 = ◊
0.5x4 - x2 - 40 = 0
 x1 = 3.16  x2 = -3.16
x3 = ◊  x4 = ◊
3x4 - 57x2 + 270 = 0
 x1 = 3  x2 = -3
x3 = 3.16  x4 = -3.16
6.5x4 + 13x2 - 227.5 = 0
 x1 = ◊  x2 = ◊
x3 = 2.24  x4 = -2.24
-3x4 - 33x2 - 30 = 0
 x1 = ◊  x2 = ◊
x3 = ◊  x4 = ◊
4.5x4 + 63x2 + 180 = 0
 x1 = ◊  x2 = ◊
x3 = ◊  x4 = ◊
9x4 + 45x2 - 450 = 0
 x1 = ◊  x2 = ◊
x3 = 2.24  x4 = -2.24
4.5x4 - 72 = 0
 x1 = 2  x2 = -2
x3 = ◊  x4 = ◊
9x4 + 9x2 - 18 = 0
 x1 = ◊  x2 = ◊
x3 = 1  x4 = -1